2018
DOI: 10.1007/s11482-018-9632-1
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in the Participants in a Community-Based Positive Youth Development Program in Hong Kong: Objective Outcome Evaluation Using a One-Group Pretest-Posttest Design

Abstract: Project BP.A.T.H.S.^has been shown to be effective in promoting positive development outcomes among Chinese adolescents in the school context. However, little is known whether the benefits can also be found in other settings. The purposes of the study was to investigate the changes in psychosocial outcomes among Hong Kong Chinese adolescents after participating in a community-based positive youth development (PYD) program. Using a one-group pretest-posttest design, junior high school students (N = 17,544) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 63 publications
5
34
0
Order By: Relevance
“…Ma, Shek, and Leung (2019) successfully replicated two previous studies (i.e. Ma, Shek, and Chen 2019) and confirmed the effectiveness of a youth program in promoting adolescents' positive youth development attributes and psychological well-being. Singer et al (2019) replicated Ray et al (2013) study and revealed that higher levels of compassion satisfaction and lower levels of compassion fatigue predicted lower rates of burnout in victim advocates.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Ma, Shek, and Leung (2019) successfully replicated two previous studies (i.e. Ma, Shek, and Chen 2019) and confirmed the effectiveness of a youth program in promoting adolescents' positive youth development attributes and psychological well-being. Singer et al (2019) replicated Ray et al (2013) study and revealed that higher levels of compassion satisfaction and lower levels of compassion fatigue predicted lower rates of burnout in victim advocates.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were revealed in Project PATHS, a positive youth development program that has been applied in Hong Kong secondary schools during the past 10 years (e.g. Ma, Shek, and Chen 2019). The research team found that adolescents in junior high schools benefit greatly from this program and displayed significant positive improvements in most of the positive youth development attributes after they participated in the positive youth development training program.…”
Section: Positive Changes After Taking Tomorrow's Leaderssupporting
confidence: 71%
See 2 more Smart Citations
“…In the Chinese context, the Project P.A.T.H.S. has been shown to promote life satisfaction in Chinese high school students in Hong Kong ( Ma et al, 2019a,b ) and China ( Zhu and Shek, 2020 ). The development and implementation of educational and intervention programs to promote students’ PYD qualities and life satisfaction would be very meaningful for helping educators and school administrators to reduce the academic stress of students and elevate their academic satisfaction.…”
Section: Discussionmentioning
confidence: 99%